2017
DOI: 10.1002/jbmr.3123
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum DHEAS Predicts Increased Fracture Risk in Older Men: The MrOS Sweden Study

Abstract: The adrenal-derived hormones dehydroepiandrosterone (DHEA) and its sulfate (DHEAS) are the most abundant circulating hormones and their levels decline substantially with age. DHEAS is considered an inactive precursor, which is converted into androgens and estrogens via local metabolism in peripheral target tissues. The predictive value of serum DHEAS for fracture risk is unknown. The aim of this study was, therefore, to assess the associations between baseline DHEAS levels and incident fractures in a large coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
14
0
3
Order By: Relevance
“…In summary, we demonstrate that high DHEA and DHEAS are associated with a lower fall risk in older men, independently of serum testosterone levels. Our previous studies also demonstrated that low serum levels of DHEA and/or DHEAS predict an increased risk of all cause and cardiovascular mortality, cardiovascular events, and fracture risk . Moreover, the genetic variants and related genes associated with serum DHEAS levels are connected to biological pathways linking DHEAS with aging.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In summary, we demonstrate that high DHEA and DHEAS are associated with a lower fall risk in older men, independently of serum testosterone levels. Our previous studies also demonstrated that low serum levels of DHEA and/or DHEAS predict an increased risk of all cause and cardiovascular mortality, cardiovascular events, and fracture risk . Moreover, the genetic variants and related genes associated with serum DHEAS levels are connected to biological pathways linking DHEAS with aging.…”
Section: Discussionmentioning
confidence: 84%
“…Further adjustments were made for total body lean mass and grip strength (n ¼ 2402 in the combined model), narrow walk (n ¼ 2387), and the combination of lean mass, grip strength, and narrow walk (n ¼ 2292 demonstrated that low serum levels of DHEA and/or DHEAS predict an increased risk of all cause and cardiovascular mortality, (28) cardiovascular events, (29) and fracture risk. (18) Moreover, the genetic variants and related genes associated with serum DHEAS levels are connected to biological pathways linking DHEAS with aging. This suggest that the molecular pathways involved in DHEAS regulation on the one hand and aging and longevity on the other hand share common genetic components, (8) further corroborating a role for DHEA and its sulfate as markers of biological aging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased cortisol levels in the mornings occur at least in the first 6 months after bereavement, often accompanied with decreased levels of dehydroepiandrosterone (DHEA) [3]. Studies have shown an increased risk for falls and fractures in older men with low levels of DHEA [32,33]. When compared with married ones, widows were more likely to demonstrate worse coping behaviour in terms of more smoking and drinking.…”
Section: Bereavement and Physiological Effectsmentioning
confidence: 99%